Musculoskeletal health of subjects with hemophilia A treated with tailored prophylaxis: Canadian Hemophilia Primary Prophylaxis (CHPS) Study. Issue 3 (13th March 2013) - Hilliard, P.; Zourikian, N.; Blanchette, V.; Chan, A.; Elliott, B.; Israels, S. J.; Nilson, J.; Poon, M.‐C.; Laferriere, N.; Van Neste, C.; Jarock, C.; Wu, J.; et al.
Summary Background Full‐dose prophylaxis is very effective at minimizing joint damage but is costly. Tailored prophylaxis has been proposed as a way of reducing costs while still protecting joints. Objective To report detailed findings in index joints of 56 subjects with severe hemophilia A entered into the Canadian Hemophilia Prophylaxis Study, and treated with tailored prophylaxis, after 13 years. Methods Boys with severe hemophilia A (< 2% factor) and normal joints were enrolled between the ages of 1 and 2.5 years. Initial treatment consisted of once‐weekly factor infusions, with the frequency escalating in a stepwise fashion when breakthrough bleeding occurred. During the first 5 years, subjects were examined every 3 months using the modified Colorado Physical Evaluation (PE) scale; subsequently, every 6 months. The Childhood Health Assessment Questionnaire (CHAQ) was administered at each visit. Results Median age at study entry was 19 months (range 12–30 months); median follow‐up was 92 months (range 2–156). The median PE score was 2, 3 and 3 at ages 3, 6 and 10 years. Persistent findings were related to swelling, muscle atrophy and loss of range of motion. The median score for each of these items (for the six index joints) was 0 at ages 3, 6 and 10 years. The median overall CHAQ score was 0 at ages 3, 6 and 10 years, indicating excellent function. Conclusions Canadian boys treated with tailored primary prophylaxis exhibit minimal joint change on physical examination and minimal functional disability.